2014
DOI: 10.1016/j.immuni.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Gpr109a, Receptor for Niacin and the Commensal Metabolite Butyrate, Suppresses Colonic Inflammation and Carcinogenesis

Abstract: SUMMARY Commensal gut microflora and dietary fiber protect against colonic inflammation and colon cancer through unknown targets. Butyrate, a bacterial product from fermentation of dietary fiber in the colon, has been implicated in this process. GPR109A (encoded by Niacr1) is a receptor for butyrate in the colon. GPR109A is also a receptor for niacin, which is also produced by gut microbiota and suppresses intestinal inflammation. Here we showed that Gpr109a signaling promoted anti-inflammatory properties in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
1,438
7
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,770 publications
(1,604 citation statements)
references
References 48 publications
(75 reference statements)
33
1,438
7
13
Order By: Relevance
“…The priming by bacterial components probably involves a combination of TLR Clinical score activation, and inflammasome activation by SCFAs occurs through their binding to the metabolite-sensing GPCRs GPR43 and GPR109A. GPR109A has previously been shown to be involved in IL-18 production 30 , and our studies here identify the inflammasome pathway for this increase. Similar to SCFAs, K þ efflux activates the inflammasome pathway in primed epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
“…The priming by bacterial components probably involves a combination of TLR Clinical score activation, and inflammasome activation by SCFAs occurs through their binding to the metabolite-sensing GPCRs GPR43 and GPR109A. GPR109A has previously been shown to be involved in IL-18 production 30 , and our studies here identify the inflammasome pathway for this increase. Similar to SCFAs, K þ efflux activates the inflammasome pathway in primed epithelial cells.…”
Section: Discussionsupporting
confidence: 50%
“…It is of great clinical relevance that lower abundance of GPR109A ligands, niacin and butyrate in gut is associated with colonic inflammation. Recently, Singh et al [170] have demonstrated an…”
Section: Scfas Induction Of Tregs By Gpr43 and Gpr109a Expressionmentioning
confidence: 99%
“…Butyrate-dependent HDAC inhibition in DCs may lead to indirect promotion of Treg cell differentiation in the colon by inducing Raldh1 expression 54) . Exposure to butyrate also confers anti-inflammatory properties to macrophages and DCs, most likely through activation of Gpr109a-dependent signaling 55) . Notably, the frequency of butyrate-producing bacteria is reduced in patients with IBD 56) .…”
mentioning
confidence: 99%